For God so loved the world : a blueprint for kingdom diversity - Strickland, Walter R.; Hartman, Dayton (B & H Academic, 2020)
Strickland and Hartman provide a blueprint for kingdom diversity. They provide historical context of our American evangelical problems with diversity, then present a public and practical theology of diversity in the Christian context.